STRATEGIC ORIENTED IMPLEMENTATION OF PROJECTS - MIHALY GOROG (NEW DELHII VIVA, 2018)
Lavishly illustrated with more than 40 figures and tables, this book effortlessly provides both theory and practical tools for thinking and working strategically throughout the project process, including mastering scope challenges and evaluating project success.
Keywords: STRATEGIC MANAGEMENT; PROJECT MANAGEMENT